Long term condition management: an expert partnership? - Brand, Sarah L. (2018)
Management of long term conditions is seen as one of the greatest challenges facing the English National Health Service currently (House of Commons Select Committee, 2014). One of the proposed solutions for this growing crisis is to support patients to manage their conditions themselves, thereby reducing hospital visits and lowering costs to the NHS overall (NHS England, 2013). Self-management necessarily involves the patient having some level of knowledge regarding their condition. In addition, there is a commitment within healthcare for patients to be involved in decision making regarding their healthcare needs with the mantra “no decision about me without me” (Department of Health, 2010) as well as development of the ‘expert patient’ agenda within healthcare (NHS Choices, 2014). In order for knowledge to be shared between health care professionals, patients and carers, knowledge boundaries must be managed within the process of knowledge sharing. This ethnographic study takes as it starting point, literature concerned with knowledge boundaries specifically, but highlights how current understanding of these boundaries is limited in some ways. In particular, issues of power and choice within the management of knowledge boundaries are inadequately explored within this body of literature which limits its applicability to contexts such as healthcare, in which power dynamics are endemic. In addition, the concepts of identity and expertise are implicated in issues of power and therefore this study seeks to explore the relationships between power, identity, expertise and knowledge in order to better understand the nature of knowledge boundaries and the dynamics of their management. This study found that issues of power were fundamentally implicated in knowledge sharing and the management of knowledge boundaries. Knowledge boundaries were found to be not only sites of struggle over knowledge, but also sites of struggle for control more generally. Whilst knowledge and power have long been associated, this study found that this relationship was complex and greater knowledge did not necessarily confer greater power on the social actor. Despite being evident in the rhetoric of healthcare, as a basis for power, expertise was redundant as more embedded social discourses remained prevalent. It is proposed that bases of social power are hierarchical in some respects as power based on one foundation can be rendered ineffective if faced with opposing power exerted by another social actor based on an alternative and more efficacious basis. This study emphasises the pervasive nature of embedded power dynamics within healthcare which concurrently facilitate conventional knowledge sharing processes and impede the development of new processes which would encourage the increased involvement of patients.